Creating GIS-Based Planning Tools to Promote Equity Through Green Infrastructure - Heckert, Megan; Rosan, Christina D. (Frontiers in Built Environment, 2018)
The Philadelphia Water Department, now known as Philadelphia Water (PW), has been coordinating with other city and private and non-profit stakeholders to install green infrastructure (GI) across the city as a means of addressing stormwater runoff as well as promoting social, economic, and environmental benefits such as improved health, job creation, and carbon sequestration. While many planning tools exist to assist in the development of green infrastructure projects, recent critiques have highlighted limitations in their considerations of non-environmental concerns, and several new planning tools have been proposed that use indexes and other need-based approaches to account for a wider range of potential program impacts. Even these new ideas, however, fail to systematically account for the possibility that not only desired GI benefits but also the impacts of specific GI projects may vary considerably from place to place. Based on our experiences with a community advisory board working to assess co-benefits of GI, we propose the inclusion of more interactive methods for incorporating community perspectives on the benefits of GI into GI planning methodologies to make them both more equitable and more responsive to community needs.